PENENTUAN UMUR EKONOMIS DUMP TRUCK HD 785-7 DENGAN MENGGUNAKAN METODA BIAYA TAHUNAN RATA-RATA PADA PT. SEMEN PADANG - Riko Ervil; Rizki Ananda Putri (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2018)
PT Semen Padang, a cement company, has equipment high investment and high operating costs, especially in raw material provision limestone, silica, clay and their distribution. The object of this research is dump truck HD 785-7 as a vehicle of raw material operated by PT. Semen Padang. According to accumulative data from July to December 2012 any failure to this vehicle will obstruct operation and cost as much as Rp.700.000.000,- . The purpose of this research is to determine economic life of dump truck HD 785-7 by using average annual cost method. This research conducted by machine specification, investment value of dump truck, fuel usage data, lubricants usage data, spare part replacement data, operational time data, dump truck service data.Based on all data, we can figure outeconomic life of dump truck HD 785-7 by using average annual cost method. After calculation process and analysing data, we concluded that economic life of dump truck HD 785-7 was 4 years, from 2011 as the purchasing year to 2014. Therefore, at the fourth year, PT. Semen Padang has 2 options: replacing the truck or do the maintenance.